2021
DOI: 10.1007/s40135-021-00269-x
|View full text |Cite
|
Sign up to set email alerts
|

The Future Is Now: Incorporating Telemedicine into Glaucoma Care

Abstract: Purpose of Review The field of teleglaucoma has expanded rapidly in recent years with several large-scale teleglaucoma screening programs in existence throughout the world. Additionally, teleglaucoma programs for use in disease management are under study. The limited access to care that resulted from the COVID-19 pandemic highlighted the need for expansion of such programs. This article reviews the literature on teleglaucoma for screening and management of glaucoma, discussing considerations for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The accelerated application of telehealth during the COVID-19 pandemic has offered options for care, but evidence of its benefits and disadvantages is mixed. Telemedicine may improve patient experience, as seen by a decreased travel burden in one review on adult glaucoma care [ 99 ]. However, “digital exclusion” of patients who lack the resources to participate in telemedicine is a growing concern and a cause of widening health inequalities [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated application of telehealth during the COVID-19 pandemic has offered options for care, but evidence of its benefits and disadvantages is mixed. Telemedicine may improve patient experience, as seen by a decreased travel burden in one review on adult glaucoma care [ 99 ]. However, “digital exclusion” of patients who lack the resources to participate in telemedicine is a growing concern and a cause of widening health inequalities [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optic disc abnormalities suggesting potential glaucoma disease showed a prevalence of 4%, although it is important to remember that the diagnosis of this pathology needs an evaluation of the optic disc by ophthalmoscopy exam with pharmacological mydriasis and instrumental examinations, such as the visual field carried and optical coherence tomography (OCT) [25]. Although the role of the digital fundus camera in glaucoma diagnosis during screening programs remains controversial due to the quality of photographs or algorithm performance, in our opinion, for the purpose of the PROTECT project, this diagnostic procedure proved to be a crude but useful evaluation to highlight the possible subjects at risk and to guide clinicians, as has been suggested recently [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In a database analysis of telemedicine use among 16.7 million beneficiaries with commercial insurance and Medicare Advantage over the first 13 weeks of the pandemic, Patel et al [52 ▪ ] observed that 9.3% of ophthalmologists used telemedicine at least once (versus 67.7% of endocrinologists and 50.0% of cardiologists), and only 2.6% of telemedicine visits were for glaucoma. While teleglaucoma has been used for years as a screening tool in remote and underserved areas [53], several barriers to its routine implementation for disease management exist [5 ▪ ,48 ▪ ,49 ▪ ,54 ▪ –61 ▪ ]. Long-term glaucoma monitoring relies upon physical examination findings (e.g., IOP measurement, gonioscopy, optic nerve assessment) and extensive ancillary testing (e.g., CCT, perimetry, and imaging of the retinal nerve fiber layer and macula) [62 ▪ ].…”
Section: Improving Glaucoma Carementioning
confidence: 99%
“…Long-term glaucoma monitoring relies upon physical examination findings (e.g., IOP measurement, gonioscopy, optic nerve assessment) and extensive ancillary testing (e.g., CCT, perimetry, and imaging of the retinal nerve fiber layer and macula) [62 ▪ ]. Currently available tools for home-based glaucoma monitoring, including rebound tonometry and remote perimetry, are either inadequately validated or limited by expense [54 ▪ ,56 ▪ ,57 ▪ ]. Poor vision, lack of access to and familiarity with digital health platforms, and poor internet connectivity may also limit patients’ ability to utilize teleglaucoma.…”
Section: Improving Glaucoma Carementioning
confidence: 99%